2013
DOI: 10.1115/1.4007547
|View full text |Cite
|
Sign up to set email alerts
|

Compressor Efficiency Variation With Rotor Tip Gap From Vanishing to Large Clearance

Abstract: Compressor efficiency variation with rotor tip gap is assessed using numerical simulations on an embedded stage representative of that in a large industrial gas turbine with Reynolds number ∼ 2 × 106 to 7 × 106. The results reveal three distinct behaviors of efficiency variation with tip gap. For relatively small tip gap (less than 0.8% span), the change in efficiency with tip gap is nonmonotonic with an optimum tip gap for maximum efficiency. The optimum tip gap is set by two competing flow processes: decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…A linear variation in axial compressor blade efficiency with tip clearance was also shown by Beheshti (2004) and Seshadri et al (2014). Seshadri et al (2014) and Sakulkaew (2013) however found that close to zero clearance the relationship becomes non-linear, resulting in an optimum, non-zero clearance. This is because shear loss increases at the casing as the tip clearance becomes very small.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A linear variation in axial compressor blade efficiency with tip clearance was also shown by Beheshti (2004) and Seshadri et al (2014). Seshadri et al (2014) and Sakulkaew (2013) however found that close to zero clearance the relationship becomes non-linear, resulting in an optimum, non-zero clearance. This is because shear loss increases at the casing as the tip clearance becomes very small.…”
Section: Introductionmentioning
confidence: 94%
“…It was shown that entropy generation due to the leakage vortex is proportional to the difference between the streamwise velocities of the two flows. Sakulkaew (2013) carried out a study of compressor efficiency variation from large to vanishing clearances. The loss variation with tip gap was found to be linear between tip clearances of 1 and 3%.…”
Section: Introductionmentioning
confidence: 99%
“…The second avenue considered by designers to increase an aircraft engine efficiency-the reduction of aerodynamic losses-implies a very stringent control of operating blade-tips/casings clearances in order to avoid any leak from higher to lower pressure stages. While a reduction of operating clearances provides a very significant improvement of the overall efficiency [19,20,21], it also unavoidably favors structural contacts between rotating and static components of the engine [22,23]. Following such contact events, a variety of complex phenomena including blade failures [24], abnormal increases of temperature [25], and even modal interactions [26,27] have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The second one is the effect of the clearance size on the compressor or the cascade performance. For example, Lakshminarayana and Horlock [18] and Peacock [24] both found that there exists an optimum clearance size that makes the performance of the compressor cascade to be the best and Lakshminarayana and Horlock [18] pointed out that this only happens when the strength of the leakage flow and the secondary flow are comparable and they can just cancel out; Sakulkaew, et al [25] also found that there is an optimum clearance at the rotor tip in an industrial gas turbine, and proposed that this phenomenon is mainly caused by the decrease of clearance flow mixing loss and increase of viscous loss in the tip clearance with the decrease of tip clearance size; in addition, Dong, et al [23] found that the leakage flow can eliminate corner separation at the stator hub, and improve the compressor performance, which has been verified by Wennerstrom [26], and McDougall [27] at the rotor tip, while Gbadebo, et al [22] revealed that the clearance flow tends to strengthen the corner separation when the clearance size is very small.…”
Section: Introductionmentioning
confidence: 99%